(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2022)
The aim of this research was to find out students’ perspective in using twitter as a tool to improve their vocabulary. The population of this research was Twitter users who are high school students. A total of 100 twitter users were included in the sample for this research. As the result of delivering questionnaires to respondents, this data result was considered as primary data. Quantitative descriptive method used to process the data. The survey method used to collect data, which entails sending out online questionnaires to the respondents. The result of the survey showed that among 100 respondents, there were 61.8% from Surabaya and 38.2% from Makassar; also 48%, 28.4%, and 23.5% come from Grade 12, 11 and 10. Result of this research revealed that using twitter is 75,89% effective as one of social networking that can be used as media to learn English in particular to improve building.